PRODUCTIVITY ANALYSIS OF ERGONOMIC CHAIR FOR OPERATOR POND MACHINE - Mukhtar, M. Nushron Ali; Mufarich, Am. (UNIPA PRESS, 2020)
there is a previous study analyzing the design of ergonomic chairs for pond machine operators, where the analysis uses the RULA method manually, Based on the results of data processing with the RULA method, it can be concluded that the posture of the ring making operator (washer) operator with a slightly bent body position has a score value 5, and the chair design based on the redesign of the pond engine operator chair shows that the final result is 3. (Mukhtar, 2018) In this study, a productivity analysis is carried out to measure the level of chair productivity by considering several aspects of work activities, The method used is the Objective Matrix (OMAX) and the determination of the score from the performance appraisal using the Analytical Hierarchy Process (AHP) method. The results obtained are Productivity increased from before, because it is still in the range of 3-10 (based on the matrix table the score 3-5 is good enough, 6-8 good and 9-10 very good) and the lowest values ​​shown in this table are 3 and 4 Based on the scores, the scores are still quite good. But there still must be improvement. Overall the level of productivity has increased compared to before. But there are still fluctuating data. This is due to the lack of uniformity in the ability of the opeator to run the pond engine in washer production.